Flexible working time arrangements and gender equality - A comparative review of 30 European countries - Plantenga, Janneke; Remery, Chantal (Luxembourg, 2010)
"Increased flexibility of working time arrangements and promotion of gender equality are two important elements in the EU’s employment policy. In many instances, increased flexibility has a positive effect on gender equality, although this is not always the case. This review from the EU Expert Group on Gender and Employment sets out the relationship between working time flexibility and gender equality and compares the state of play in 30 European countries (EU-27 and EEA/EFTA). It gives an overview of working time flexibility throughout Europe as well as in-depth analysis of flexibility in terms of length and organisation of working time. Information is also provided on the regulatory framework and recent policy developments in the field. In addition, the review comprises a detailed statistical annex."